Probiotics and amelioration of periodontitis: significant roles of Lacticaseibacillus casei DS31 - Liu, Yang; Wu, Peng; Li, Yizhen; Chen, Xiaofeng; Wang, Ling; Su, Yanjun; Luo, Lianzhong; Cai, Yihuang; Huang, Qinmiao; Tang, Xu (Frontiers in Microbiology, 2025)
BackgroundPeriodontitis, a chronic gum disease caused by Porphyromonas gingivalis infection, if left untreated, can result in tooth loss, alveolar bone loss, halitosis and other oral health complications.MethodsTo investigate the preventive and therapeutic effects of Lacticaseibacillus casei DS31 from the large yellow croaker (Larimichthys crocea) on periodontitis, three experimental models—biofilm, cellular, and animal models—were established to systematically evaluate its efficacy. First, we sought to clarify the effect of DS31 against P. gingivalis biofilm. Then, the investigation entailed a comprehensive examination of the immunomodulatory effects of heat-inactivated probiotics on inflammation-inducing cells. Finally, the impact of probiotics on gingival tissue and alveolar bone was evaluated using an established periodontitis rat model.ResultsThe results demonstrated that bacteria suspension or cell-free supernatant of L. casei DS31 effectively inhibited P. gingivalis biofilm formation and eradicated existing biofilms, thereby reducing the secretion of pro-inflammatory cytokines (TNF-α, IL-6 and IL-1β) and inflammatory mediators (NO). Microcomputed tomography (micro-CT) and histopathological analysis revealed that supplementation with BS-DS31 or CFS-DS31 mitigated alveolar bone loss and increased bone mineral density in the experimental animals. The secretion of inflammatory factors (TNF-α, IL-1β, IL-6 and IL-8) in the gingival tissue of the rats was reduced.ConclusionLacticaseibacillus casei DS31 demonstrates significant potential for alleviating periodontitis and could serve as a promising probiotic candidate for incorporation into functional foods and oral health therapeutic applications.